2015
DOI: 10.1002/aenm.201501754
|View full text |Cite
|
Sign up to set email alerts
|

(040)‐Crystal Facet Engineering of BiVO4 Plate Photoanodes for Solar Fuel Production

Abstract: mobility and fast charge recombination, which result in limitations during practical application. Because the solar light conversion effi ciency ( η ) [ 15 ] is directly proportional to the product of the solar light absorption effi ciency ( η abs ), charge separation effi ciency ( η sep ), and surface charge transfer effi ciency ( η trans ). The decoration of the cocatalyst [ 16 ] and the introduction of porosity to increase surface area [ 17 ] have been studied for practical usage of PEC with increased η abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
104
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(105 citation statements)
references
References 38 publications
(106 reference statements)
1
104
0
Order By: Relevance
“…

rate (≈12 cm 2 V −1 s −1 ) compared to TiO 2 (0.5 cm 2 V −1 s −1 ), a robust hole migration length (≈150 nm) relative to Fe 2 O 3 (2-4 nm), and attractive photostability. [15][16][17][18][19] Considering the specific WO 3 , recent studies have revealed that nanosheets exposed with {001} facets show better catalytic activity than the other facets due to the highest oxygen atom density. In this regard, with an aim to further breakthroughs for pursuing excellent energy conversion performance in high-potential WO 3 photoanode, integrated dismantling aforesaid restricting factors are greatly imperative.

As such, tailoring crystal facets is a conventional strategy for optimizing the catalytic performance in the case of various semiconductor materials because heterogeneous reactivity depends strongly on the surface atomic configuration and bonding environment that can be altered by controlling crystalline facets.

…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…

rate (≈12 cm 2 V −1 s −1 ) compared to TiO 2 (0.5 cm 2 V −1 s −1 ), a robust hole migration length (≈150 nm) relative to Fe 2 O 3 (2-4 nm), and attractive photostability. [15][16][17][18][19] Considering the specific WO 3 , recent studies have revealed that nanosheets exposed with {001} facets show better catalytic activity than the other facets due to the highest oxygen atom density. In this regard, with an aim to further breakthroughs for pursuing excellent energy conversion performance in high-potential WO 3 photoanode, integrated dismantling aforesaid restricting factors are greatly imperative.

As such, tailoring crystal facets is a conventional strategy for optimizing the catalytic performance in the case of various semiconductor materials because heterogeneous reactivity depends strongly on the surface atomic configuration and bonding environment that can be altered by controlling crystalline facets.

…”
mentioning
confidence: 99%
“…[15][16][17][18][19] Considering the specific WO 3 , recent studies have revealed that nanosheets exposed with {001} facets show better catalytic activity than the other facets due to the highest oxygen atom density. [15][16][17][18][19] Considering the specific WO 3 , recent studies have revealed that nanosheets exposed with {001} facets show better catalytic activity than the other facets due to the highest oxygen atom density.…”
mentioning
confidence: 99%
“…[20] Varieties of morphological BiVO 4 , which are generally enclosed by lowindex {111}, {110}, or {100} planes, were formed through control of the synthetic methods and experimental conditions. [21][22][23] The photocatalytic behavior of BiVO 4 is highly dependent on its surface structure, in which photogenerated electrons and holes can be preferentially separated and accumulated on {010} and {110} facets, respectively, via the driving force created by the different band energies of the two facets. [24,25] Herein, we report the synthesis unprecedented 30-faceted BiVO 4 polyhedra predominantly surrounded by high-index {132}, {321}, and {121} facets.…”
mentioning
confidence: 99%
“…Designing photocatalyst systems of multiple scales to overcome these competing effects has been proposed and successfully demonstrated. [17,57] For example, it has been reported that electron and hole transfer occurs on different crystallographic planes of both rutile and anatase TiO 2 microcrystal. [47] Crystallinity and defects: Crystallinity is considered as a complex factor for reactivity of photocatalyst.…”
Section: Wileyonlinelibrarycommentioning
confidence: 99%